Trauma-induced coagulopathy and critical bleeding: the role of plasma and platelet transfusion. Issue 1 (December 2017) - Ishikura, Hiroyasu; Kitamura, Taisuke
Abstract Hemorrhage is responsible for 30 to 40% of all trauma-related mortality. Among adult trauma patients, 94% of hemorrhage-related deaths occur within 24 h and approximately 60% of these deaths within 3 h of hospital admission. Therefore, appropriate initial fluid resuscitation for bleeding is crucial to avoid preventable trauma-related death. In particular, the resuscitation strategy must be designed to complement prompt correction of anemia, coagulopathies, and thrombocytopenia. Conventional damage control resuscitation (DCR) of patients with severe trauma and massive hemorrhage is usually begun with rapid infusion of 1000 to 2000 mL of crystalloid fluids with subsequent transfusion of type O or uncross-matched red blood cells (RBCs) without plasma such as fresh frozen plasma (FFP) or platelets (PLTs). However, this DCR technique often leads to several adverse events such as abdominal compartment syndrome, acute respiratory distress syndrome, multiple organ failure, and dilutional coagulopathy. Simultaneous transfusion of FFP and PLTs along with the first units of RBCs while minimizing crystalloid infusion was recently recommended as a renewed DCR strategy. This aggressive RBC transfusion with FFP and PLTs is not only essential for the correction of coagulopathies and thrombocytopenia but also has the potential to ensure a good outcome in trauma patients. Additionally, it is important to maintain the resuscitation ratios of FFP/RBC and PLT/RBC. Most recently, DCR has been advocated for rapid hemorrhage control through early administration of a mixture of FFP, PLTs, and RBCs in a balanced ratio of 1:1:1.